Development Strategy for a Medium-Sized Economy - Teubal, Morris (Econometrica, 1971)
In this paper an analysis of optimum structural change and optimum trade policies for a developing economy is carried out in the context of a neoclassical three-sector open model of economic growth. The sectors are agriculture, industry, and industry, and the conditions for staged and direct patterns of development are derived. Some implications of a foreign exchange bottleneck are also derived. 1 THIS PAPER DEALS with the development strategy of a medium-sized economy facing downward sloping world demand schedules for its agricultural exports and fixed world prices for industrial goods. An optimal development strategy involves the determination of rates of capital accumulation, patterns of specialization, and structure of foreign trade. In a small economy-one facing world-determined prices for all goods-the pattern of specialization depends on resource endowments while the structure of foreign trade is adjusted to the accumulation target. In a medium-sized economy, on the other hand, the optimum patterns of both trade and specialization may have to be determined simultaneously with the rate of growth of the economy. The specialization decisions facing a developing economy involve, on the one hand, the question of the desirability of a policy of industrialization and, on the other, the efficient strategy of industrial growth. The latter must choose between consumer goods industries and capital goods industries (or between light industries and heavy industries); between import substituting industrialization and final-demand induced industrialization. The foreign trade strategy, on the other hand, must contain a strategy of exports and one for imports; the former should point out the efficient mix between agricultural exports and nontraditional exports (such as exports of manufactured consumer goods), while the latter should indicate the proportion of capital-goods imports in total imports. The basic model is developed in Sections 2 to 5. Section 6 analyzes the changes in the overall development strategy required for endogeneous growth acceleration, while Section 7 deals with the development strategy under a foreign exchange bottleneck.